Designing self-sustaining early generation seed supply systems: The must-dos - Akpo, Essegbemon; Opie, Hellen; Ojiewo, Christopher Ochieng; Desmae, Haile; Muricho, Geoffrey; Midingoyi, Soul; Ntare, Bonny; Ayana, Amsalu; Ininda, Jane; Mourik, Tom A. van; Schagen, Boudy van; Okori, Patrick (Wageningen University & Research, 2022)
Shortages in the supply of quality early generation seed (EGS) of new and improved varieties, particularly of dryland cereals and legumes is a major challenge because of the business models.This triggers the following questions: what EGS business models would sustainably avail quality parent seed? To investigate this, we documented 16 EGS interventions. We found that pre-securing seed market ahead of production played important role in the successful seed business. Taking different forms (e.g., pre-orders, demand forecasting, pre-aggregation of demand, joint planning,contractual agreement), it brings confidence to EGS producers to continuously invest in the business and make it profitable. For sustainable EGS production and supply in sub-Saharan Africa, we advocate for market assurance in advance. Two guiding principles are also suggested and four recommendations formulated.